IMPLEMENTASI APLIKASI SISTEM ONLINE SINGLE SUBMISSION (OSS) TERHADAP PERKEMBANGAN LAYANAN PERIZINAN UMKM DI DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU KOTA MOJOKERTO - Mita Suwarni, Siti; Rinayuhani, Tri Ratna; Hasan Afandi, Ahmad (MAJAPAHIT POLICY, 2022)
From year to year technology advances. In the field of public services, it will continue to develop and improve its useto serve community needs. In order to reduce bureaucratic problems regarding permit processing which seems complicated and too muchTaking time in Indonesia, the government launched a new system, namely OSS (online single submission). OSS is a licensing service systemelectronically integrated businesses. There are still many UMKM in Mojokerto City who have not received business permits, which is why the governmentIt is hoped that it will further socialize how important it is to obtain a business license for the progress of business carried out by business actors and for the success of businessthey get legal legality. Implementation is an important stage in the public policy process. Policy programs must be in placeimplement it to achieve the desired impact or goal.